Tinjauan Yuridis Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta Terhadap Pemblokiran Situs Streaming Film Ilegal - Muhammad, Fachri; Permana, Raditya; Habibaty, Diana Mutia (Mavisha: Law and Society Journal, 2024)
This research uses normative research methods and library research through a statute approach. The statute approach refers to Law Number 28 of 2014 concerning Copyright. Film is a creative work that is protected, therefore violating this by pirating films and distributing them over the internet is an illegal act. This can harm the creators or copyright holders, both in terms of moral rights and economic rights. Law enforcement against perpetrators of piracy who distribute films through illegal streaming sites can result in penalties such as imprisonment or fines if the creators or copyright holders file a lawsuit or report. On the other hand, if there are no prosecutions or reports regarding this violation, the government, based on Article 56, has the right to take preventive measures in the form of blocking. The reason the government implements blocking as a form of legal protection for copyright is outlined in Article 1, which states that copyright is the exclusive right of the creator that arises automatically based on the declarative principle once a creation is manifested in a tangible form. The research results indicate that Law Number 28 of 2014 concerning Copyright has regulated violations committed by illegal movie streaming sites in the form of prevention through closure or access blocking. The government's role in preventing the circulation of pirated films through the blocking of illegal streaming sites is not enough, considering that these illegal streaming sites are still accessible to users.   Penelitian ini meggunakan metode penelitian normatif dan kepustakaan (library research) melalui pendekatan Perundang-undangan (statute approach), Pendekatan perundang-undangan mengacu kepada Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta. Film merupakan karya cipta yang dilindungi oleh sebab itu pelanggaran dengan membajak film dan menyebarkannya melalui internet merupakan perbuatan yang dilarang, hal ini dapat merugikan pencipta atau pemengang hak cipta baik itu hak secara moral maupun hak ekonomi. Penegakan hukum bagi para pelaku pembajakan yang menyebarkan film melalui situs-situs streaming film ilegal dapat dikenakan sanksi berupa pidana atau denda apabila pihak dari pencipta atau pemengang hak cipta melakukan penuntun atau pelaporan. Sebaliknya jika tidak ada penuntutan atau pelaporan mengenai pelanggaran ini maka pemerintah bardasarkan pasal 56 berhak melakukan pencegahan berupa pemblokiran. Hasil penelitian menunjukan bahwa Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta telah mengatur tentang pelanggaran yang dilakukan oleh situs-situs streaming film ilegal dalam bentuk pencegahan berupa penutupan atau pemblokiran akses. Peran pemerintah dalam mencegah peredaran film bajakan melalui pemblokiran situs-situs streaming film ilegal ini belum cukup, melihat situs-situs streaming film ilegal masih dapat diakses oleh penggunanya.